Пассивная испарительно-конденсационная система охлаждения лазера - Gershuni, A. N.; Nishchik, A. P. (PE "Politekhperiodika", Book and Journal Publishers, 2012)
A special heat pipe for ensuring the thermal regime of the active element of an optical quantum generator (laser) under heat sink by radiation has been developed. It is shown that under the simulated fuel element power of 50 W wall temperature in the heat pipe heating zone does not exceed 30°C, and the emergency heating prevents deep freezing of the entire system in the absence of heat generation of the object itself.